1. All five statements below are true.
  2. None of the four statements below are true.
  3. Both of the statements above are true.
  4. Exactly one of the three statements above is true.
  5. None of the four statements above are true.
  6. None of the five statements above are true.

closed as off-topic by Brandon_J, Alconja, Omega Krypton, Peregrine Rook, Glorfindel Apr 1 at 5:53

This question appears to be off-topic. The users who voted to close gave this specific reason:

  • "This looks like a puzzle you found elsewhere. For content you did not create yourself, proper attribution is required. If you have permission to repost this, please edit to include (at minimum) where it came from, then vote to reopen. Posts which use someone else's content without attribution are generally deleted." – Brandon_J, Alconja, Omega Krypton, Peregrine Rook, Glorfindel
If this question can be reworded to fit the rules in the help center, please edit the question.

  • 1
    $\begingroup$ Ha! Great puzzle! $(+1)\,\color{orange}{\bigstar}$ $\endgroup$ – Mr Pie Mar 31 at 5:40
  • 3
    $\begingroup$ Is this an original puzzle? $\endgroup$ – Dr Xorile Mar 31 at 15:04
  • 3
    $\begingroup$ brainly.in/question/8878122 $\endgroup$ – Paul Evans Mar 31 at 22:26
  • 5
    $\begingroup$ @PaulEvans' link suggests that the puzzle has been posted elsewhere before. We require sources to be listed to avoid plagerism. Even if you are the author of the other link, then just let us know that. Or you could cite the other link and state that you came up with it independently. It's a policy of this forum $\endgroup$ – Dr Xorile Apr 1 at 0:36
  • 3
    $\begingroup$ @giorgircheulishvili Have a look, it's not modified. It's word-for-word identical. $\endgroup$ – Paul Evans Apr 1 at 12:14

This is the line of thought I followed:

Statement #3

is impossible because of #1 and #2 contradicting each other (let's consider only the last three statements, for simplicity). So, #3 must be false.

As a consequence,

#1 must be false.

If #4 were true, then #2 must be true (by exclusion), but this would imply that #4 itself is false. Then,

#4 is false.

If #5 were true,

then #2 must be false. So far, this holds.
If #5 were false, then #2, by exclusion, must be true. But this implies that #3 is true too, which is a contradiction, as seen above.
Then #5 is true, and #2 is false.


#6 is false because it being true would imply that #5 is false.

In conclusion,

there is only one true statement, as said in the title, and is #5.


True statement is

5th statement


1 is false(only 5 is true)
2 is false(5 is true)
3 is false(both above are false)
4 is false(all are false)
6 is false(5is true)

  • 1
    $\begingroup$ (A space after >! is not required. However, you cannot follow a spoiler line immediately with a non-spoiler line; it will break the formatting. A blank line after the spoilered line(s) suffices.) $\endgroup$ – Rubio Mar 30 at 21:07

Another nice way to approach this puzzle is by constructing chains of implications. We know there's only one true statement, so if one statement implies another one, then it's false.

  • Firstly, $3\Rightarrow1\Rightarrow6\Rightarrow5$, so $3$ and $1$ and $6$ are false.

  • Since $3$ and $1$ are not true, $4\Leftrightarrow2$, so they're both false.

  • The only option left is $5$, so this is the answer.

  • $\begingroup$ Except it's also possible to uniquely determine each statement's truth value without assuming the title question implies any fact. $\endgroup$ – aschepler Mar 31 at 18:40

The correct one is



1 is not possible, as only one is true.
2 is not possible, as it makes 4 true.
3 is not possible for similar reasons.
4 is not true as it makes one of 1, 2 or 3 true as well.
6 is self-contradictory.


Same answer as everyone else, slightly different reasoning

1 must be false (if true then 6 would be true and contradict it).

=> 3 is false.

As a result, if 2 were true then 4 would also be true, contradicting "which one statement", so 2 is false.

=> 4 is false

Trivially 5 is true, 6 is false.


My Answer

Statement 5 is the true statement.


If Statement 1 is true then Statement 6 is true; however, statements 1 and 6 cannot both be true as they are mutually contradictory; therefore, Statement 1 is false.
If Statement 1 is false then Statement 3 is also false.
If 2 is true then 4 would be false; However, if statement 4 is false then statement 2 is negated. It is logically impossible for statement 2 to be true.
If 1, 2, and 3 are false then 4 is also false.
If 1, 2, 3, and 4 are false then 5 is true.
Finally, if 5 is true then 6 is false.
Hence, statement 5 is the only true statement.
edit: you can also eliminate statements 1 and 3 immediately because they imply that more than one statement is true while the questions states that there is only one true statement.


I have used substitution to determine the only true statement.

Indeed, I started by writing the logic equivalents of each statement.

$$1 \leftarrow 2 \land 3 \land 4 \land 5 \land 6$$ $$2 \leftarrow \lnot 3 \land \lnot 4 \land \lnot 5 \land \lnot 6$$ $$3 \leftarrow 1 \land 2$$ $$4 \leftarrow (1 \land \lnot 2 \land \lnot 3) \lor ( \lnot 1 \land 2 \land \lnot 3) \lor ( \lnot 1 \land \lnot 2 \land 3)$$ $$5 \leftarrow \lnot 1 \land \lnot 2 \land \lnot 3 \land \lnot 4$$ $$6 \leftarrow \lnot 1 \land \lnot 2 \land \lnot 3 \land \lnot 4 \land \lnot 5$$

From this, a simple replacement in $6$ gives us

$$6 \leftarrow 5 \land \lnot 5$$

Which really is just,

$$6 \leftarrow F$$

From there, you simply substitute the result in the other equations

$$1 \leftarrow 2 \land 3 \land 4 \land 5 \land F $$ $$2 \leftarrow \lnot 3 \land \lnot 4 \land \lnot 5 \land \lnot F $$

Which gives us

$$ 1 \leftarrow F $$

Again, substitution...

$$3 \leftarrow F \land 2$$ $$4 \leftarrow (F \land \lnot 2 \land \lnot 3) \lor ( \lnot F \land 2 \land \lnot 3) \lor ( \lnot F \land \lnot 2 \land 3)$$ $$5 \leftarrow \lnot F \land \lnot 2 \land \lnot 3 \land \lnot 4 $$

Simplifying to

$$1 \leftarrow F $$ $$2 \leftarrow \lnot 4 \land \lnot 5 $$ $$3 \leftarrow F $$ $$4 \leftarrow (F) \lor (2 \land T) \lor (F) $$ $$5 \leftarrow T \land \lnot 2 \land T \land \lnot 4 $$ $$6 \leftarrow F $$

At this point, we can simply rewrite as:

$$1 \leftarrow F $$ $$2 \leftarrow \lnot 4 \land \lnot 5 $$ $$3 \leftarrow F $$ $$4 \leftarrow 2 $$ $$5 \leftarrow \lnot 2 $$ $$6 \leftarrow F $$

This gives us the satisfaction that, in fact,

$$ 2 \leftarrow \lnot 2 \land \lnot \lnot 2 $$

Which is a contradiction, thence

$$ 2 \leftarrow F $$

Giving us the solution

$$5 \leftarrow T $$

  • 1
    $\begingroup$ Welcome to Puzzling SE! $\endgroup$ – SteveV Mar 31 at 23:55
  • $\begingroup$ Very formal! A superb answer! $\endgroup$ – Mr Pie Apr 2 at 1:27

Alright, here's my try. I think I have a fairly straightforward explanation.

1. All five statements below are true.
2. None of the four statements below are true.
3. Both of the statements above are true.
4. Exactly one of the three statements above is true.
5. None of the four statements above are true.
6. None of the five statements above are true.

We can instantly eliminate

Statements 1, 3, and 4.


Well, they all say that there is another true answer. The design of the question precludes this from being true - "Which one is the true statement?" (emphasis mine).

This leaves

Statements 2, 5, and 6. We need a way to make two of them false. Statement 6 cannot be the true statement - it would make statement 5 true, which would make statement 6 false. Statement 2 and 5 can be true, if the other is false. Ignoring previously eliminated statements, statement 2 says statement 5 is false. Statement 5 says statement 2 is false. However, if statement 2 were true, statement 3 is also true.

Thus, as a final answer,

Statement 5 would work.


Not the answer you're looking for? Browse other questions tagged or ask your own question.